Family Medicine in Small Communities - Bailey, K.A. (1987)
This article is an off-the-cuff commentary on one practice in a city of 40,000 people. This city is in a largely agricultural area. The article stresses the pluses: the continuity of care and the more interesting and variegated nature of family practice here. There are negatives, as well: the more limited social life and the problems relating to employment for one's spouse. Patient confidentiality is more difficult to maintain, as is one's own privacy. Generally it is a busier and more challenging life, which I heartily recommend.